Further results on Gram's Law - Trudgian, TS (2009)
This thesis shows that Gram's Law and the Rosser Rule (methods for locating zeroes of the Riemann zeta-function) fail in a positive proportion of cases. A weaker version of Gram's Law is shown to be true in a positive proportion of cases. Also included are theorems on Turing's Method and its extensions to Dirichlet L-functions and Dedekind zeta-functions.